"Hot Guys" in Tel Aviv: Pride Tourism in Israel. Issue 1 (1st March 2020) - Kama, Amit; Ram, Yael
Abstract: The LGBTQ+ (lesbian, gay, bisexual, transgender, and questioning) community is warmly embraced by the city of Tel Aviv. This phenomenon is exemplified by the fact that the Tel Aviv City Hall has been taking a leading part in the organization, financing, and promotion of Pride parades and events in recent years. The present article analyzes a quantitative survey of overseas participants in the 2016 Pride events in Tel Aviv. It explores the motivations, attitudes, satisfaction, and behaviors of tourists, both LGBTQ+ and non- LGBTQ+. The results show that Tel Aviv is perceived as gay friendly by all participants, regardless of their affiliation with the LGBTQ+ community. We discuss the advantages of being a gay-friendly city via high visibility and social inclusion. Finally, we address 'pinkwashing', an umbrella term employed to describe the efforts by Israeli authorities to promote a positive image of Israel despite its questioned geopolitical reputation.